Establishment and Maintenance of Conventional and Circulation-Driven Lung-Resident Memory CD8+ T Cells Following Respiratory Virus Infections - Takamura, Shiki; Kohlmeier, Jacob E. (Frontiers in Immunology, 2019)
Antigen-specific CD8+ tissue-resident memory T cells (TRM cells) persist in the lung following resolution of a respiratory virus infection and provide first-line defense against reinfection. In contrast to other memory T cell populations, such as central memory T cells that circulate between lymph and blood, and effector memory T cells (TEM cells) that circulate between blood and peripheral tissues, TRM cells are best defined by their permanent residency in the tissues and their independence from circulatory T cell populations. Consistent with this, we recently demonstrated that CD8+ TRM cells primarily reside within specific niches in the lung (Repair-Associated Memory Depots; RAMD) that normally exclude CD8+ TEM cells. However, it has also been reported that circulating CD8+ TEM cells continuously convert into CD8+ TRM cells in the lung interstitium, helping to sustain TRM numbers. The relative contributions of these two mechanisms of CD8+ TRM cells maintenance in the lung has been the source of vigorous debate. Here we propose a model in which the majority of CD8+ TRM cells are maintained within RAMD (conventional TRM) whereas a small fraction of TRM are derived from circulating CD8+ TEM cells and maintained in the interstitium. The numbers of both types of TRM cells wane over time due to declines in both RAMD availability and the overall number of TEM in the circulation. This model is consistent with most published reports and has important implications for the development of vaccines designed to elicit protective T cell memory in the lung.